How automobile parts supply network structures may reflect the diversity of product characteristics and suppliers' production strategies. Issue 1 (2015) - Kito, Tomomi; New, Steve; Ueda, Kanji
Abstract: This study quantitatively investigates the heterogeneous nature of the structures and characteristics of real-life auto-parts supply networks, through complex network analysis of large-scale empirical data. Comprehensive data containing "who-supplies-what-to-whom" information successfully highlights the wide diversity of product characteristics, companies' production capabilities, and also their resulting strategies. Furthermore, by using an advanced complex network analysis technique, the supply networks are projected into a different information space, generating another network that elucidates the proximities between product types and between companies' production strategies. Analysis of this network provides profound insights into how supply network structures may emerge reflecting various factors.